The use of the press in learning areas. (Journal of Parents and Teachers, 2025)
The article discusses the Basic Curriculum Design and the role of newspapers in schools, which should be central in communicating activities, subjects, and programs. It also presents the press in the area of nature and its impact on general objectives and content blocks
Keywords: Newspaper; DCB; Protagonist; school